The influence of tundish heating and purging on inclusion formation - Souza Junior,Jayme Alves de (2015)
Steel with high cleanliness requirements require an accurate control of the non-metallic inclusions, such as its quantity, morphology, chemical composition and size distribution. The continuous casting tundish has a fundamental role in steel cleanliness, avoiding its reoxidation by air and ladle slag that retain inclusions, as well as aiding the removal of those same inclusions along the continuous casting (Sahai, 2008). To perform the study, IF steel samples were collected in RH at the start, in the middle and at the end of the continuous casting of the tundish's first heat in three different conditions of tundish processing, alternating between heating and purging. These samples had their inclusions characterized by MEV/EDS using the ASCAT (Automated Steel Cleanliness Analysis Tool) technology. The results showed that more than 90% of the oxide inclusions generated in that type of steel are Al2O3 and AlTi. It was also observed that there is an increase of steel inclusions originating from RH in the tundish and that area fraction and average inclusionary density decreases along the continuous casting in two of the processing conditions.